Financial reporting as indicator of financial management of enterprise - Купешова, Б.; Когут, О. (Journal of Economic Research & Business Administration, 2017)
The financial reporting is examined as an interlink between an enterprise and his users. From предстaвленой in the financial reporting of information, the future of enterprise depends. In a management an enterprise the system of indicators is by the system the second order, along with the system of instruments entering in the complement of the system of indicative management. Indicator it is qualitatively-quantitative description of the examined process or phenomenon. He shows a change in a dynamics or deviation from a normative value. In the strategic management of activity of enterprise the most well-known system of indexes is the Balanced system of indexes of Нортонa- Кaплaнa (BSC). BSC unites financial and unfinancial indicators. BSC contains having a special purpose indexes wrap-round all strategically important spheres of activity of organization; forms причинно- следственные connections between all groups of indexes; serves as an instrument for realization of strategies of organization and increase of dataware of acceptance of administrative decisions; forms indicators for a management by organization and т. of п. BSC foremost created for the leaders of higher level of management and owners of enterprises.